As tecnologias digitais e a construção dos sentidos de ser professor : um estudo autoetnográfico da coordenação do PIBID Inglês - Silva, Fabione Gomes da (2022)
Digital technologies have transformed the way we think, act in the world and (re)construct ourselves in the social spaces for living, reconfiguring the way we behave, receive, process information and react in face of the multiple manifestations of the language in communicative interaction, in the most varied social spheres, whether in the public or private domain. This doctoral research had as its main objective to understand the relationship of digital technologies with the construction of the meanings of being a teacher. In the study, I relate my history of life with the digital technologies and in this interweaving process I investigated how my theoretical and methodological choices as a Coordinator of the Pibid English and the technologies are connectedmaking relationships between my personal life experiences and the acquired learnings (re)constructed over the years, in addition to highlighting these constructions of meanings in the discourses and practices of the other members of the Pibid English. In the thesis, I adopted autoethnography as the qualitative research method. In autoethnography, the researcher seeks to systematically investigate and analyze a described experience, in order to understand a cultural phenomenon (ELLIS; ADAMS, 2019). Autoethnography makes possible reflections about how we think and do research, establish relationships and live. In this sense, in autoethnography, we use the experience of the self to try to explain, describe and reflect upon cultural realities, understood as identity representations (CHANG, 2008). The research is affiliated to the epistemology of Meaning Making of Literacies and Multiliteracies Pedagogy. The dimensions of learning from a social, historical and cultural perspective, of digital technologies, of English language teaching and teacher training make up the other building blocks of the theoretical foundation. In the course of the research, the primary information emerged from my memories, experiences, personal and professional records, as internal data (CHANG, 2008), for the writing of the autobiographical section. The external instruments, generated in the Pibid English cultural community, such as the autoethnographic diary, the logbooks and video and audio recordings materialized the ethnographic section of the thesis. In writing the narrative, I adopted Hayler's analytical strategy (2011) as a methodological principle to construct meanings and establish meanings from the data, throughout all sections, relating the information generated to my theoretical framework. The analysis and interpretation of the data showed that digital technologies are at the heart of my resignifications of being an English teacher and are inextricably linked to the representations of plural and heterogeneous identities, to critical, transgressive and political reflection, to social commitment, as well as to the planning and execution of pedagogical activities experienced by the Pibid English community.